Vertical sexual habitat segregation in a wintering migratory songbird. Issue 1 (7th January 2021) - Cooper, Nathan W; Thomas, Mark A; Marra, Peter P
Abstract: Sexual habitat segregation during the wintering period is a widespread phenomenon and has important implications for the ecology and conservation of migratory birds. We studied Black-and-white Warblers ( Mniotilta varia ) wintering in second-growth scrub and old-growth mangrove forest in Jamaica to quantify sexual habitat segregation and explore whether patterns of habitat occupation have consequences on physical condition. We used this information along with a body size analysis and simulated territorial intrusions to assess whether behavioral dominance or habitat specialization was responsible for habitat segregation. Based on standardized capture data, we found that females were more abundant than males in both scrub and mangrove forests. Foraging observations, however, suggested vertical segregation within each habitat, with females foraging primarily near the ground and males in the mid-canopy and canopy, indicating that our sex ratio estimates may be biased. Using 2 measures of body condition, we show that males were in better body condition than females, regardless of habitat. We found that males were on average slightly larger than females, and home range analysis and simulated territorial intrusions indicated that males were more territorial than females. We argue that the observed vertical sexual habitat segregation is likely caused by behavioral dominance rather than habitat specialization. Winter body condition is known to carry over to affect migration timing, reproductive success, and annual survival in other songbirds, and therefore sexual habitat segregation may have important implications for year-round population dynamics in Black-and-white Warblers. Lay Summary: Female Black-and-white Warblers were partially excluded from the middle and upper parts of the forest canopy by more dominant males. This vertical habitat segregation may have resulted in poor body condition in females compared to males.